English Teacher Development and Training in The Utilization of AI For Personalized Learning and Remedial Based on Online Formative Assessment Data - Nurjamin, Lucky Rahayu; rasetyo, Agung; Pamungkas, Sapto; Munawir, Ahmad Farhi; Andini, Anggi Setia; Nisa, Asri Ainun (Fakultas Kewirausahaan Universitas Garut, 2025)
In the era of globalization and digitalization, English language proficiency is becoming increasingly important. English serves not only as a tool for international communication but also as a key to accessing global knowledge, technology, and information. Therefore, efforts to improve the quality of English teaching in Indonesia through the use of educational technology are essential. Training on the development and utilization of AI for personalized learning and remediation based on formative data assessments was boldly conducted with a practical and participatory approach. It explained the concepts of personalized and remedial learning, as well as an introduction to AI-based tools that can be used in the English language learning process. The use of artificial intelligence in education offers significant opportunities to improve the efficiency and effectiveness of the learning process. This training focused on two key aspects of personalized learning and remediation: teachers can use data to identify students' strengths and weaknesses. AI enables the creation of specific learning content tailored to students' ability levels, creating a more engaging learning experience.